2015
DOI: 10.3389/fpls.2015.00726
|View full text |Cite
|
Sign up to set email alerts
|

Companion cropping with potato onion enhances the disease resistance of tomato against Verticillium dahliae

Abstract: Intercropping could alleviate soil-borne diseases, however, few studies focused on the immunity of the host plant induced by the interspecific interactions. To test whether or not intercropping could enhance the disease resistance of host plant, we investigated the effect of companion cropping with potato onion on tomato Verticillium wilt caused by Verticillium dahliae (V. dahliae). To investigate the mechanisms, the root exudates were collected from tomato and potato onion which were grown together or separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
5
37
0
Order By: Relevance
“…Additional analyses showed that companion cropping with potato onions decreased the disease incidence and index (Fig. 1), confirming the results of the previous study5. These results indicated that companion cropping with potato onions increases the accumulation of substances related to resistance, thereby increasing the resistance of tomato plants against V. dahliae.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Additional analyses showed that companion cropping with potato onions decreased the disease incidence and index (Fig. 1), confirming the results of the previous study5. These results indicated that companion cropping with potato onions increases the accumulation of substances related to resistance, thereby increasing the resistance of tomato plants against V. dahliae.…”
Section: Discussionsupporting
confidence: 89%
“…For example, root interactions between maize and soybean increase the resistance of soybean to Cylindrocladium parasiticum 10, and maize and pepper interactions enhance maize resistance to Bipolaris maydis 9. Similarly, in a previous study, we have shown that tomato and potato onion interactions enhance tomato resistance to V. dahliae by up-regulating disease resistance-related genes under the tomato/potato onion companion cropping5. To explore the physiological defense responses of tomato to V. dahliae infection, we examined changes in the content of total phenol, lignin, GSH, and MDA, and the enzymatic activities of SOD, POD, PPO and PAL, all of which are key enzymes related to disease resistance12122.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations